Helping from home: Singaporean youth volunteers with migrant‐rights and human‐trafficking NGOs in Singapore. Issue 2 (28th August 2017) - Yea, Sallie
Abstract: Social science literature on development volunteering has mainly focused on the interstices between overseas travel experiences and organised placements, with a particular focus on youth. To date, this literature has not engaged with development volunteering that takes place within one's "home country" where subjects of helping are nonetheless racially and developmentally inscribed "Others", such as refugee groups and exploited or trafficked migrants. This paper explores the motivations for and meanings of youth volunteering in development "at home". The site for this examination is volunteers with NGOs oriented to migrant rights and human trafficking in Singapore. The paper makes a case for recognition of a more complicated geography of volunteering in development which is inclusive of development issues and subjects at home. Following this, the paper argues that this expression of development volunteering complicates existing characterisations, principally as volunteers express opposition to socially and state sanctioned discourses of service learning through development. Therefore, it is important to consider the political and social context of development volunteering to understand the motivations and meanings attached to development volunteering.